Órgãos específicos da administração da falência e da recuperação judicial das empresas - Filardi, Rosemarie Adalardo (2008)
The present work has as its aim to study in details the three agencies created especially for the bankruptcy administration and the judicial recovery of companies in Brazil: the Creditors Committee, the Judicial Administrator and the Creditors Meeting. The current Brazilian law on bankruptcy and recovery of companies - law 11,101/05 - altered substantially the functions and the form of action of the agencies analyzed in this study, aiming at a bigger participation of creditors in the corresponding proceedings and introducing in the system the judicial recovery of companies which allows that viable companies facing economic-financial difficulties may be able to reorganize themselves and guarantee their continuity in the market, taking into account their importance in modern society. On the other hand, once some activity is considered unfeasible, the company must be cured. The objectives guiding the judicial recovery of companies are provided for in article 47 of the mentioned law and have the specific purpose of preserving the company, encouraging the economic activity and the promotion of its social function. In this way, we tried to demonstrate with this work that the joint action of all agencies connected to the bankruptcy administration will enable to achieve the principle substantiating the new Brazilian bankruptcy regime: the principle of preservation of the companies